B.03 The Canadian neurology graduate survey. (17th June 2016) - Murray, BJ; Major, P; Poppe, A; Murphy, C; Jenkins, M; Nicolle, M; Watling, C; McMillan, HJ; Yeung, M; Callen, D; Briemberg, H; Tang-Wai, DF; et al.
Abstract : Background: Planning for neurology training necessitated a reflection on the experience of graduates. We explored practice characteristics, and training experience of recent graduates.Methods: Graduates from 2010-2014 completed a survey.Results: Response rate was 37% of 211. 56% were female. 91% were adult neurologists. 65% practiced in an outpatient setting. 63% worked in academics. 85% completed subspecialty training (median 1 year). 36% work 3 days a week or less. 82% took general call (median 1 night weekly). Role preparation was considered very good or excellent for most; however poor or fair ratings were 17% in advocacy and 8% in leadership. Training feedback was at least "good" for 87%. Burnout a few times a week or more was noted by 5% (6% during residency, particularly PGY1 and 5). 64% felt overly burdened by paperwork. Although most felt training was adequate, it was poor or fair at preparing for practice management (85%) and personal balance (55%). Most conditions were under-observed in training environment. Many noted a need for more independent practice development and community neurology.Conclusions: Although our training was found to be very good, some identified needs included advocacy training, and more training in general neurology in the longitudinal outpatient/community settings.